2019
DOI: 10.1016/j.breast.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Combination of peripheral neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio is predictive of pathological complete response after neoadjuvant chemotherapy in breast cancer patients

Abstract: The immune system seems to play a fundamental role in breast cancer responsiveness to chemotherapy. We investigated two peripheral indicators of immunity/inflammation, i.e. neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), in order to reveal a possible relationship with pathological complete response (pCR) in patients with early or locally advanced breast cancer treated with neoadjuvant chemotherapy (NACT).We retrospectively analyzed 373 consecutive patients affected by breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 57 publications
8
106
3
1
Order By: Relevance
“…Graziano et al [27] showed that PCR rates were higher in patients with NLR low /PLR low than patients with NLR high /PLR high (OR = 1.98; 95%CI 1.01-3.89; p = 0.044).…”
Section: Results On Nlr and Pcrmentioning
confidence: 99%
See 4 more Smart Citations
“…Graziano et al [27] showed that PCR rates were higher in patients with NLR low /PLR low than patients with NLR high /PLR high (OR = 1.98; 95%CI 1.01-3.89; p = 0.044).…”
Section: Results On Nlr and Pcrmentioning
confidence: 99%
“…Studies including All BC Molecular Subtypes: the PCR rate in the function of NLR was the primary objective in seven studies [22][23][24][25][27][28][29]. In all studies (except for two without definition), PCR was defined as the complete disappearance of invasive tumors in breast and lymph nodes (patients with residual ductal carcinoma in situ were also considered to have achieved PCR: ypT0/is pN0).…”
Section: Results On Nlr and Pcrmentioning
confidence: 99%
See 3 more Smart Citations